Deciphering non-canonical ubiquitin signaling: biology and methodology - van Overbeek, Nila K.; Aguirre, Tim; van der Heden van Noort, Gerbrand J.; Blagoev, Blagoy; Vertegaal, Alfred C. O. (Frontiers in Molecular Biosciences, 2024)
Ubiquitination is a dynamic post-translational modification that regulates virtually all cellular processes by modulating substrate function, localization, interactions and turnover of thousands of substrates. Canonical ubiquitination involves the enzymatic cascade of E1, E2 and E3 enzymes that conjugate ubiquitin to lysine residues giving rise to monomeric ubiquitination and polymeric ubiquitination. Emerging research has established expansion of the ubiquitin code by non-canonical ubiquitination of N-termini and cysteine, serine and threonine residues. Generic methods for identifying ubiquitin substrates using mass spectrometry based proteomics often overlook non-canonical ubiquitinated substrates, suggesting that numerous undiscovered substrates of this modification exist. Moreover, there is a knowledge gap between in vitro studies and comprehensive understanding of the functional consequence of non-canonical ubiquitination in vivo. Here, we discuss the current knowledge about non-lysine ubiquitination, strategies to map the ubiquitinome and their applicability for studying non-canonical ubiquitination substrates and sites. Furthermore, we elucidate the available chemical biology toolbox and elaborate on missing links required to further unravel this less explored subsection of the ubiquitin system.